A dynamic simulation platform for fault modelling and characterisation of building integrated photovoltaics. (December 2021) - Lin, Wenye; Ma, Zhenjun; Li, Kehua; Tyagi, V.V.; Pandey, A.K.
Abstract: This paper presents the development and validation of a building integrated photovoltaic (BIPV) simulation platform which can introduce and characterise main faults of BIPV systems. The coupling of the electrical circuit with thermal balance, and the introduction of different faults and their interactions with broken/active protection diodes are among the main contributions of this study. Through comparison with the data measured from a real BIPV installation, it was found that this platform is able to provide an acceptable prediction of the performance of BIPV systems. The design and test of a series of scenarios demonstrated that this platform was capable to simulate and characterise dynamic faulty operations of BIPV systems influenced by various faults. It was found that short-circuit current, gradient information and inflection point in the current-voltage (I–V) curve can be utilised to discriminate the aging and medium partial shading faults with corresponding broken/active bypass diodes. The open-circuit voltage and inflection point in the I–V curve, and the PV cell temperature can be used to distinguish the short-circuit fault in a PV string and inter-string short-circuit fault, with corresponding broken/active blocking diodes. Hotspot phenomenon can also be observed if a minor partial shading fault was introduced in the simulation. Highlights: A building integrated PV simulation platform for fault modelling was developed. Typical PV faults and their interaction with protection diodes were characterised. Electrical circuit and thermal balance were coupled to simulate PV systems. Inflection points is the key to discriminating broken/active protection diodes. Hotspot phenomenon can be simulated by introducing a minor partial shading fault.